Patterns of Perception in Policy Formulation: Content and Trust in Compilation of the 2020 Revised APBD Draft in Makassar City - Irfan Ali; Nurdin Nara; Rusdi; Didik Iskandar (LEGAL BRIEF, 2022)
The pattern of perception is the result of the perception of individual actors which can develop through interactions between actors in the process of formulating public policies. The formulation of the ABPD change consists of actors who have the interests of both the government and the legislature to reach an agreement. The purpose of this research is to find out the pattern of perceptions between actors in the formulation of the 2020 Revised APBD in Makassar City. The research method used is a descriptive qualitative model that seeks to explain phenomena in depth through interviews, observations, and field documentation. The technique of analyzing data from research results is carried out through data triangulation so that the data obtained can be relevant to existing concepts. The results of the study show that the perception pattern in the formulation of the Makassar City APBD draft among the actors involved has various perceptions which causes no agreement between the actors. This can be seen from two main aspects, namely content and level of trust. the substance of the draft APBD The proposed changes are considered not fully oriented towards the public interest and are considered to have unclear aims and objectives. The lack of clarity on the objectives of the activities to be carried out in the proposed revised APBD has not been able to create a good level of trust for all actors, especially for the legislative group. So in conclusion it is necessary to discuss the budget which focuses on issues that are oriented to the public interest.